Leisure time physical activities among adult attendees at a primary health care clinic - Abdul Rahman, Hejar; Iskandar, Nur Hazrina; Lim, Wai Kong (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2007)
Objectives: This cross-sectional study was undertaken to determine the leisure-time physical activities of adult attendees in a rural health clinic in July 2002. Methods: Simple random sampling method of the clinic register was used. Data was collected via a face-to-face interview using a pre-tested questionnaire. Results: A majority (73%) of the attendees performed leisure-time physical activity. The majority were between 20 to 29 years (p<0.05), females (p>0.05), Kadazan, Iban and Orang Asli (p<0.05), single (p>0.05), had attained tertiary education (p<0.05) and were employees with monthly income of more than RM1500 (p>0.05). They were also free from chronic illnesses. The most common activities were walking, aerobic dancing and gardening. Physical and mental wellness, advice from doctor and support from family and friends were the reasons for performing these activities. The reasons for not performing leisure physical activity were (i) being too busy, (ii) already active at workplace, and (iii) being unwell. Conclusions: Sustained community interventions in the community could prove useful to encourage individuals to carry out leisure-time physical activities.